A STUDY ON THE CONSTRAINTS FACED BY THE BANK AND THE FARMERS WITH REGARD TO CREDIT LENDING AND REPAYMENT IN MAHBUBNAGAR DISTRICT OF TELANGANA - P. RADHIKA, VARSHA SURVE, B.GANESH KUMAR and (The Journal of Research, PJTSAU, 2019)
Rural indebtedness is an age-old problem in India. In the nineteenth century, commercial banking was non-existent in rural areas, and farmers were completely in the hands of usurious moneylenders. Starting from the days of British rule, the central government has been striving to expand institutional lending to the rural agricultural sector. In recent decades, efforts in this direction have intensified and today, there is a vast network of institutions providing credit for agriculture (Mehta and Malhotra 2014) (Misra and Dhal 2010).